Bootstrap 4 responsive web design : a step-by-step practical course enabling you to nail Bootstrap and make your web designs responsive - Moreto, Silvio (Packt Publishing, 2016)
Unearth the potential of Bootstrap with step-by-step guidance. About This Book An applied guide exploring web application development with Bootstrap 4 Learn responsive web design and discover how to build mobile-ready websites with ease Become an expert in Bootstrap framework, and speed up frontend development and prototyping through real-life examples Who This Book Is For If you're a web developer with little or no knowledge of Bootstrap, then this course is for you. The course offers support for version 4 of Bootstrap; however, it will offer support for version 3 as well. So, you will be ready for whatever comes your way. Prior knowledge of HTML, CSS, and JavaScript is expected. What You Will Learn Discover how to use Bootstrap's components and elements, and customize them for your own projects Understand the framework's usage in the best way with the recommended development patterns Use Sass to customize your existing themes Apply the Bootstrap mobile-first grid system and add responsiveness and aesthetic touches to image elements Customize the behavior and features of Bootstrap's jQuery Plugins extensively Style various types of content and learn how to build a page's layout from scratch by applying the power of Bootstrap 4 Work with content, such as tables and figures In Detail Bootstrap framework's ease-of-use (along with its cross-browser compatibility, support for mobile user interfaces, and responsive web design capabilities) makes it an essential building block for any modern web application. With the first module, plunge into the Bootstrap frontend framework with the help of examples that will illustrate the use of each element and component in a proper way. You will get a better understanding of what is happening and where you want to reach. Also, you will gain confidence with the framework and develop some very common examples using Bootstrap. All these examples are explained step by step and in depth. The second module is a comprehensive tutorial; we'll teach you everything that you need to know to start building websites with Bootstrap 4 in a practical way. You'll learn about build tools such as Node, Grunt, and many others. You'll also discover the principles of mobile-first design in order to ensure that your pages can fit any screen size and meet responsive requirements. Learn Bootstrap's grid system and base CSS to ensure that your designs are robust and that your development process is speedy and efficient. Right from the f ...